On‐and off‐site Raman study of rock‐shelter paintings at world‐heritage site of Bhimbetka. (16th July 2012) - Ravindran, T. R.; Arora, A. K.; Singh, M.; Ota, S. B.
<x xml:space="preserve">Abstract</x> Rock‐shelter paintings of Bhimbetka world‐heritage site near Bhopal, India have been investigated using a portable Raman spectrometer. These paintings in the rock shelters belong to periods starting from pre‐historic to the 19th century AD (Gond period). In addition, tiny fragments of pigments (100–200 µm in size) extracted from some of the artworks were also studied in laboratory using a micro‐Raman spectrometer and analyzed using energy‐dispersive X‐ray analysis for elemental composition. Based on the Raman spectra and the elemental analysis mineral‐based pigments such as calcite, gypsum, hematite, whewellite, and goethite could be identified. A comparison of the spectra recorded on‐site using a light‐weight portable spectrometer with those using laboratory equipment is also made and discussed. Copyright © 2012 John Wiley & Sons, Ltd.